L’Impact de la décentralisation des entités territoriales sur l’évolution du couvert forestier : cas de la concession de l’INERA Yangambi (RDC) de 2002 à 2015 - BOHOLA LUFUKARIBU.,; LOSINGI, LINGOMBE; LOBELA MAINGOLO,; LISIKO BOYEMBA, (IJRDO-Journal of Applied Science, 2019)
The impact of the decentralization of the territorial entities on the evolution of the forest covers of the INERA Yangambi concession between 2002 and 2015. The objective of this study is to quantify the mutations of the units that the concession knows following the opening roads, shifting cultivation on slash, practices observed in the exploitation of forest resources (embers manufacturing). The supervised classification compiled with the field missions made it possible to delimit the different units of occupation of the ground. . The data used are Landsat satellite images. Between 2002 and 2015, the surface area of ​​the different land use units underwent substantial changes, resulting in a decline in the mature forest class, an increase in secondary forest, fallow and crop fields. Thus, the mature forest, which occupied 69.4% of the Concession area in 2002, was reduced to 31.47% in 2015. As for the classes of secondary forest, fallow and crop fields which occupied 9.6% and 18, 9% of the area in 2002 rose by 31.95% and 35.99% in 2015, an increase of 22.36% of secondary forest and 17.09% of class fallow and fields of culture. The itinerant farming on brulis, the galloping demography, the opening of the roads are the major causes of these mutations.